The Cosmo-Skymed Second Generation Sar Antenna Electrical Power Chain and Platform Power Distribution - Scorzafava E.; Gianninoto G.; Cantamessa M.; Zanella P.; Carlani D.; Scione E. (E3S Web of Conferences, 2017)
This paper presents the Electrical power Subsystem (EPS) of the COSMO-SKYMED SECOND GENERATION (CSG) spacecraft, regarding the design and development of the electronics for power generation, conditioning and distribution. It provides a detailed description of the power equipment’s and of the Photovoltaic Assembly (PVA). It will be also shown how the design of the power conditioning and distribution electronics has taken advantage of the Leonardo (former Finmeccanica) heritage on Power Management and Distribution (PMD) for scientific platforms [1], [3]. The design characteristics of the EPS elements are described. A summary of the main performances is given, including a glance to the EMC aspects, which are very important in the definition and characterization of the design of a high power SAR system.